2020
DOI: 10.1111/cod.13661
|View full text |Cite
|
Sign up to set email alerts
|

In vivo demonstration of immunologic cross‐reactivity to octylisothiazolinone in patients primarily and strongly sensitized to methylisothiazolinone

Abstract: Background: Notwithstanding that concomitant exposure to different isothiazolinone derivatives may result in concomitant sensitization, clinical and animal studies have suggested cross-reactivity between these derivatives, notably between methylisothiazolinone (MI) and octylisothiazolinone (OIT). Objective: To investigate if patients sensitized to MI show cross-reactions to OIT and/or to benzisothiazolinone (BIT) by applying the concept of the re-test method. Patients And Methods: From March to October 2019 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
3
11
0
1
Order By: Relevance
“…In 2017, Craig et al reported that BIT reactions occur most often in isolation and independently of other isothiazolinones as a result of independent sensitization. This is in contrast to patients that react to OIT, where many also react to another isothiazolinone, most commonly MI 19,20 . This is further supported by Holden and Sabroe who found similar results 21 .…”
Section: Discussionsupporting
confidence: 62%
“…In 2017, Craig et al reported that BIT reactions occur most often in isolation and independently of other isothiazolinones as a result of independent sensitization. This is in contrast to patients that react to OIT, where many also react to another isothiazolinone, most commonly MI 19,20 . This is further supported by Holden and Sabroe who found similar results 21 .…”
Section: Discussionsupporting
confidence: 62%
“…Although debated, and initially considered unlikely, 24 clinical studies have suggested that, besides cosensitization through concomitant exposure, cross‐reactivity between both these derivatives may also occur 25 . An animal study using a modified local lymph node assay 26 equally supported this hypothesis and, recently, Russo and Aerts 27 confirmed, in vivo, by using the retest model, that humans, at least those strongly sensitized to MI, effectively show cross‐reactivity to OIT. This implies that, in daily practice, it is important to counsel patients sensitized to MI to avoid not only MI‐ but also OIT‐containing products.…”
Section: Discussionmentioning
confidence: 99%
“…A first and likely explanation is increased exposure, and thus potential concomitant sensitization to BIT, rather than cross‐reactivity. Several arguments are in favour of this: (a) contrary to the derivatives MI, MCI, and OIT, which all have a very similar chemical structure, BIT differs by an additional benzene bicyclic ring, making cross‐reactivity less likely; (b) several studies have previously found that less than 10% of MI‐sensitized patients coreacted positively to BIT 22,28 ; (c) the recent study based on the “retest” model confirmed that, in contrast to OIT, cross‐reactivity between MI and BIT is rather unlikely 27 ; (d) the main reported sources of exposure to BIT, notably household detergents and water‐based paints, are also frequent sources of exposure to MI, rendering concomitant sensitization again more plausible 29,30 ; and (e) the possibly increased use of BIT in noncosmetic products, such as detergents or paints, or even gradual replacement of MI in some of these products, equally favours concomitant sensitization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Não é possível dizer se a sensibilização primária nestes casos terá sido por contacto com produtos cosméticos, dada a sua presença em inúmeros produtos deste tipo, nomeadamente em toalhitas de limpeza 8 . A reatividade cruzada entre os vários compostos do grupo é um assunto em debate 6 . No entanto, estão descritos casos de doentes que após sensibilização por contacto vieram a desenvolver sintomas cutâneos e respiratórios quando expostos ao mesmo composto na tinta industrial 9 .…”
Section: Discussionunclassified